2018
DOI: 10.1097/qad.0000000000001757
|View full text |Cite
|
Sign up to set email alerts
|

Individual and community-level risk factors for HIV stigma in 21 Zambian and South African communities

Abstract: Objectives Describe the prevalence and determinants of HIV stigma in 21 communities in Zambia and South Africa. Design Analysis of baseline data from the HPTN 071 (PopART) cluster-randomised trial. HIV stigma data came from a random sample of 3859 people living with HIV. Community-level exposures reflecting HIV fears and judgements and perceptions of HIV stigma came from a random sample of community members not living with HIV (n=5088), and from health workers (n=851). Methods We calculated the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 30 publications
(41 reference statements)
0
45
2
Order By: Relevance
“…The social context and HIV services in all the communities in both countries have been described elsewhere [ 38 ]. An ancillary study on stigma was undertaken, which provides additional information on stigma experiences in health facilities and levels of stigma in different communities, also described elsewhere [ 35 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The social context and HIV services in all the communities in both countries have been described elsewhere [ 38 ]. An ancillary study on stigma was undertaken, which provides additional information on stigma experiences in health facilities and levels of stigma in different communities, also described elsewhere [ 35 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some factors resulting in delayed uptake of ART are linked to broader health service delivery challenges that impede progress in providing treatment to everyone living with HIV, including access to and availability of drugs [ 29 33 ]. The barriers to treatment associated with the health service may be compounded by, for example, the persistence of HIV-related stigma which affects a person’s ability to access care and other demands on time due to making a livelihood or caring for children at home [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…HIV stigma can undermine ART adherence [12][13][14][15][16][17] and is a frequently reported barrier to adherence in sub-Saharan Africa [13]. HIV stigma is common in both Zambia and South Africa, with over 35% of PLHIV reporting some type of stigma [18]. Whilst ART adherence is consistently found to be worse among individuals experiencing stigma than among those who do not [19][20][21][22][23][24][25], a 2013 review concluded that all but one study was at risk of bias, and most had not used validated exposure or outcome measures [19].…”
Section: Introductionmentioning
confidence: 99%
“…To create the three variables, respondents who disagreed or never experienced stigma on all the questions related to that variable were grouped as 'never experiencing' that type of stigma. Those agreeing or experiencing stigma on ≥1 question were categorised as 'ever experiencing' that type of stigma [18]. Our stigma measures were aligned with standardised measures that were approved by the UNAIDS' monitoring and evaluation reference group (MERG) in 2014 [18,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Our study show that internalised and externalised HIV stigma and social norms around adolescent and youth sexuality remain a huge challenge to delivering HIV prevention, even in these high HIV burden rural settings [35][36][37]. Young people involved in this research brought a nuanced understanding of the intersection between poverty and lack of opportunity, and the gender and intergenerational power imbalances to the intervention development process [38,39].…”
Section: Discussionmentioning
confidence: 80%